Analisis strategi komunikasi pemasaran Kedai Ngopi Dhisik dalam menciptakan ketenaran merek melalui instagram - Dilla Amalia Muntaha; Ario Mukti Lazuardi Anggomulyo; Muhammad Aras (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the marketing communication strategy of the coffee shop dhisik in creating brand fame through Instagram. This is because business competition in the food and beverage industry is increasingly competitive and offers almost the same types of beverage products so consumers are confused about deciding which coffee drink product to consume. This study uses the SOSTAC concept to analyze marketing communication strategies through social media. The research approach is qualitative and the research is analyzed descriptively. The data collection technique used in-depth interviews and the data validity technique used source triangulation and theoretical triangulation so that the research data became valid. The results of the research findings indicate that the marketing communication strategy applied is that the owner of the 'ngopi dhisik' shop takes the action of posting/uploading photo and video content on Instagram social media by providing captions as information. The posted content displays price promotions and unique types of coffee drinks to attract attention and create the fame of the 'ngopi dhisik' brand.